Elderly depression: A public health dilemma; challenges and opportunities - Soumya Swaroop Sahoo; Udit Kumar Panda; Vikas Bhatia (Wolters Kluwer Medknow Publications, 2017)
India is undergoing a demographic transition that has resulted in rapid growth of the elderly population. This enormous growth has mandated an urgent need for the development of mental health services. Elderly depression is a significant contributor to morbidity and mortality in this age group. The Global Burden of Disease report 2015 outlines depression as the third leading contributor to global disability measured as disability adjusted life years (DALYs). Early identification, diagnosis and initiation of treatment can provide the elderly an opportunity to improve their quality of life and a considerable reduction in the morbidity and mortality. This public health challenge can be addressed by social support and engaging primary health care providers in providing patient centred care. The philosophy of geriatric medicine is not only to add years to life but to help the elderly attain the desired life span with minimal distress and disability.